(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2008)
In situ implants containing Progesterone (PRG) were prepared by using biodegradable Poly (DLlactide- co-glycolide) polymer. Dimethyl sulfoxide (DMSO) was used as an aprotic solvent in this implant formulation. This system was prepared by dissolving a water insoluble and biodegradable polymer (PLGA) in a biocompatible organic solvent (DMSO) and then the drug progesterone was added to the polymer solution to produce the drug solution. When the PLGA-PRG solution (0.5 ml) was injected subcutaneously into rat (weight 130g), the solvent dissipated into the surrounding tissue leading phase separation and subsequent coagulation of the polymer & drug to form an implant in situ. The implants were removed from the rat after one hour and stored in freezing condition. The digital photographs of the in-situ formed implants obtained after 1hour shows the evidence of the formation of the implants. Two formulations of implants were made. One contained 10% of progesterone and the other 20%. In vitro dissolution studies of progesterone was performed at static condition in ethanol-water mixture (30:70) at 37°C for 30 days. The implants of 20% progesterone loading showed about 65% release and the implants of 10% loading showed 56% release within 30 days. The release mechanism from these implants resembles closely to Higuchian pattern and first order. The release rate was found faster from the implants with higher drug loading of 20% progesterone, compared to implants of 10% drug loading. Key words: Biodegradable; Implant; Biocompatible; Sustained Release Dhaka Univ. J. Pharm. Sci. 6(2): 99-103, 2007 (December)